Interactive Media Design for Augmented Reality–Based Hajj Ritual Learning Using Muslim Sadiq 3D - Annisa Sofia Mujahidah (International Forum of Researchers and Lecturers, 2025)
Learning Hajj rituals requires innovation to overcome the limitations of available media, one of which is through the utilization of the integration of the Android platform with Augmented Reality technology. The Muslim Sadiq application on smartphones displays 3D objects related to the practice of Hajj rituals. This study aims to explain the design of interactive media based on Augmented Reality as an innovation in learning Hajj rituals, expected to improve student understanding through a more visual, interactive, and contextual learning experience. This media design method adopts two stages of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), namely the needs analysis and media design stages. This study reveals that learning Hajj rituals requires interactive and applicable media to overcome the gap between theoretical understanding and the practice of Hajj worship in real life. The designed media utilizes AR technology to create a simulation of Hajj implementation and supports experience-based learning. Although the design has considered technical and pedagogical aspects, this media is still in the design stage and has not been tested or implemented directly. Therefore, further research is needed to assess the effectiveness of this media in learning Hajj rituals.